Does Quantification of Carotid Plaque Surface Irregularities Better Detect Symptomatic Plaques Compared to the Subjective Classification?. (8th May 2019) - Rafailidis, Vasileios; Chryssogonidis, Ioannis; Grisan, Enrico; Xerras, Chrysostomos; Cheimariotis, Grigorios‐Aris; Tegos, Thomas; Rafailidis, Dimitrios; Sidhu, Paul S.; Charitanti‐Kouridou, Afroditi
Abstract : Objectives: To evaluate the interobserver agreement of color Doppler ultrasound (CDUS) and contrast‐enhanced ultrasound (CEUS) for quantification of carotid plaque surface irregularities and to correlate objective and subjective measures with stroke occurrence. Methods: This work was an observational study involving 54 patients with 62 internal carotid artery or carotid bulb plaques (31 symptomatic) undergoing CDUS and CEUS between February 2016 and February 2018, with retrospective interpretation of prospectively acquired data. Plaques were included if causing moderate (50%–69%) or severe (70%–99%) stenosis based on velocity criteria, and their surface was classified as smooth, irregular, or ulcerated based on CEUS. The surface irregularities were quantified in the form of a surface irregularity index by 2 observers, based on CDUS and CEUS. The surface irregularity index was evaluated for interobserver agreement with CDUS and CEUS and correlated with the occurrence of stroke, as was the subjective characterization of the plaque surface. Results: Color Doppler ultrasound and CEUS showed good interobserver agreement (intraclass correlation coefficients, 0.979 and 0.952, respectively). Plaques were characterized as smooth in 30.6% of cases, irregular in 50%, and ulcerated in 19.4%. The subjective classification of the plaque surface did not correlate with stroke occurrence ( P > .05, χ 2 ). Surface irregularity index values were significantly higher for symptomatic plaques with both CDUS and CEUS ( P < .05). Conclusions: Color Doppler ultrasound and CEUS can quantify carotid plaque surface irregularities with good interobserver agreement. The resulting quantitative measure was significantly higher in symptomatic plaques, whereas the subjective characterization of plaque surface failed to differ between symptomatic and asymptomatic plaques.